Controlled feeding experiments with juvenile alligators reveal microscopic dental wear texture patterns associated with hard-object feeding - Winkler, Daniela E.; Iijima, Masaya; Blob, Richard W.; Kubo, Tai; Kubo, Mugino O. (Frontiers in Ecology and Evolution, 2022)
Dental wear analyses are classically applied to mammals because they have evolved heterodont dentitions for sophisticated mastication. Recently, several studies have shown a correlation between pre-assigned and analytically inferred diet preferences in extant reptiles through dental microwear texture analysis (DMTA), a method using quantitative assessment of microscopic wear marks to reconstruct diet material properties. First tentative applications of DMTA to extinct reptiles have followed. However, for large and small mammals, microwear analyses have undergone a long time of ground-truthing through direct feeding observations, stomach content analyses, and feeding experiments. Such data are currently lacking for reptiles, but necessary to further extend DMTA especially to Archosauria, as application to dinosaurs could be of great interest to the scientific community. We here present data from a pilot feeding experiment with five juvenile American alligators (Alligator mississippiensis). Each individual received a diet of assumed different hardness for ~4 months: crocodile pellets (control), sardines, quails, rats, or crawfish. All individuals initially received the same pellet diet, and we found them to show similar dental microwear texture patterns before they were switched to their designated experimental diet. From the first feeding bout on, dental microwear textures differed across the diets. The crawfish feeder showed consistently higher surface complexity, followed by the rat feeder. Quail and fish-feeding resulted in similar wear signatures, with low complexity. Fast tooth replacement and selective tooth use likely affected microwear formation, but we were able to detect a general hard (crawfish, rat) versus soft (quail, fish) DMTA signature. Such patterns can support identification of hard-object feeding in the fossil record.